Integration of Geopsychiatry: A Synthesis and Analysis of Case Studies and Field Research on Possession Trance Disorder (PTD) in Indonesia - Pardomuan Robinson Sihombing (Awatara Publisher, 2026)
Background: In Indonesia, the treatment of the phenomenon of Possession Trance Disorder (PTD) and visual hallucinations is often hampered by the dichotomy between medical and spiritual approaches. Many interventions fail because they rely solely on theoretical assumptions without sufficient empirical field evidence. Objective: This study aims to dissect the etiology, mechanisms, and effectiveness of mystical phenomena therapy using primary data (case studies and experiments) and to formulate integrative intervention models and methods. This study was conducted using the Systematic Review of Primary Studies method, following the PRISMA 2020 protocol. Inclusion criteria are strictly limited to primary data articles (case studies, qualitative field studies, EEG experiments) published between 2019 and 2025. Results: Analysis of 15 selected primary studies showed that PTD consistently appeared as a comorbidity of undiagnosed dysthymia and trauma. Neurophysiological evidence (EEG) confirms that trance is a biological hyperarousal condition, not just hysteria. Therapies based on Indigenous Psychology (Kawruh Jiwa) and cultural distraction techniques (Drawing/Murottal) have proven effective in real clinical settings. Conclusion: The most effective treatment model is an integrated approach or hybridization: medical biological stabilization combined with the restructuring of meaning through local psychology.